2017
DOI: 10.5152/tjsm.2017.081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Three Decade Changes in Physical Fitness Characteristics of Turkish Children Aged Between 11 and 12

Abstract: Objectives: In order to examine the changes in physical characteristics and motor abilities of Turkish children aged 11 or 12 years old, data collected in three different periods (1983 to 1985, 1999 to 2003 and the year 2013) were compared in the present study. Material and Methods: Data for girls (age 11, n=187; age 12, n=181) and boys (age 11, n=435; age 12, n=392) were obtained from Eurofit tests applied between the years 1983 and 1985 in four different cities; between the years 1999 and 2003 in İzmir, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…When compared with the matching data of another study (11 age n=112 girls and n=344 boys; 12 age n=85 girls and n=251 boys) (Haslofça, Kutlay, & Haslofça, 2017) in our country to determine sports predisposition; all mean values, body height and handgrip strength of the participants in our study were found to be similar, and it was observed that body weight, BMI, skinfold thickness values were lower, and vertical jump and flamingo test values were better.…”
Section: Discussionmentioning
confidence: 55%
“…When compared with the matching data of another study (11 age n=112 girls and n=344 boys; 12 age n=85 girls and n=251 boys) (Haslofça, Kutlay, & Haslofça, 2017) in our country to determine sports predisposition; all mean values, body height and handgrip strength of the participants in our study were found to be similar, and it was observed that body weight, BMI, skinfold thickness values were lower, and vertical jump and flamingo test values were better.…”
Section: Discussionmentioning
confidence: 55%
“…Teknolojideki gelişmelere paralel olarak; sosyal yaşam ve oyun alanlarının yetersizliği, ulaşım kolaylığı, televizyona ve bilgisayar oyunlarına bağımlılık, zararlı besin tüketimine olan yönelimler, hareketsizliği ve obeziteyi beraberinde getirmektedir. Fiziksel hareket eksikliğinin çocukların fiziksel potansiyelinde önemli kayıplara neden olduğunu ortaya koyan birçok çalışma vardır (Haslofça, Kutlay, & Haslofça, 2017;Whaley, Brubaker, Otto, & Armstrong, 2006). Bu durum dolaylı olarak ülkelerin üst düzey sporcu yetiştirme potansiyellerini de olumsuz etkilemektedir.…”
Section: Introductionunclassified